EXAMINING SPEECH ACTS IN ENGLISH TEXTBOOKS: SIGNIFICANCE AND IMPLICATIONS FOR EFL INSTRUCTION - widiatmoko, Paulus (The Journal Of English Teaching For Young And Adult Learners, 2025)
Pragmatic competence is a crucial component of cultural understanding, encompassing the ability to select and interpret expressions and utterances in specific context of communication. This aspect of language instruction often receives insufficient attention due to teacher priority on language forms over its functions. The primary objective of this study was to identify types of speech acts in the dialogues of the first and fourth editions of the "New Interchange" series written by Jack C. Richards and Jonathan Proctor. Utilizing Searle’s classifications of speech acts, the results indicated that both editions provided a range of suitable speech acts for beginner learners. Moreover, the fourth edition presented a greater frequency of speech acts in a relatively proportional manner compared to its predecessor, suggesting an enhancement in the instructional material's capacity to foster pragmatic competence. To maximize this potential, teachers should use effective strategies that include explicitly teaching speech acts, providing guided practice, and creating opportunities for meaningful interaction. By doing so, learners are facilitated to manage the complexities of language use in different sociolinguistic contexts, thereby improving their communication skills.